The Effect of Academic Anxiety and Stress on The Risk of Functional Dyspepsia Among Pre-Clinical Medical Students: A Literature Review - Meisya Devi Ardhana; Hafshah Yasmina Abidah (Riviera Publishing, 2026)
Functional dyspepsia is a functional gastrointestinal disorder commonly found in the productive-age population, including medical students. This condition is characterized by symptoms such as epigastric pain, postprandial fullness, early satiety, nausea, bloating, and a burning sensation in the upper abdomen (heartburn), without any identifiable organic abnormalities. Various studies have shown that psychological factors, particularly anxiety and academic stress, contribute to the occurrence of functional dyspepsia through the brain–gut axis mechanism. This literature review aimed to analyze the relationship between anxiety and academic stress and the incidence of functional dyspepsia among medical students. The method used was a literature review based on a systematic search of scientific databases, primarily PubMed, as well as relevant international journals. The articles included were published between 2016 and 2026. A total of 11 articles that met the inclusion criteria were analyzed using a narrative synthesis approach.